Status of substance use among undergraduate medical students in a selected government medical college in Puducherry - An explanatory mixed method study - N Lokesh; K Sivaranjini; Sathish Rajaa; Balaji Bharadwaj; Swaroop Kumar Sahu (Wolters Kluwer Medknow Publications, 2023)
Background: Studies have shown increase in health-risking behavior and a decline in health-promoting behavior among medical students during their stay in medical school. This study aims to determine the prevalence and reason for substance abuse among the undergraduate medical students in a selected medical college in Puducherry. Material and Methods: This was a facility-based explanatory mixed method study conducted from May 2019 to July 2019. Assessment of their substance abuse was done using ASSIST questionnaire. Substance use was summarized as proportions with 95% CI. Results: A total of 379 participants were included in the study. The mean age of the study participants was 20 years (± 1.34). The most prevalent substance use was alcohol (10.8%). About 1.9% and 1.6% of students surveyed consume tobacco and cannabis, respectively. Conclusion: Facilitating factors for substance use as perceived by the participants were stress, peer pressure, easy availability of substances, socialization, curiosity, and awareness knowledge about safe limits of alcohol and tobacco.